A rare complication: Right ventricular lead perforation abutting the left anterior descending artery through the left ventricle and the septum. Issue 3 (27th October 2022) - Mililis, Panagiotis; Saplaouras, Athanasios; Konstantinidou, Eleni; Papakonstantinou, Konstantinos; Rorris, Fillipos; Mpatsouli, Athina; Dragasis, Stylianos; Vlachos, Konstantinos; Charitos, Christos; Xydonas, Sotirios
Abstract: Background: Cardiac perforation is an uncommon complication of transvenous pacemaker implantation typically occurring through the apex. Case summary: We report a case of patient, in whom ventricular lead perforation was confirmed 6 days after implantation of a dual chamber pacemaker. The ventricular lead was perforating the ventricular septum, near the left anterior descending artery, exiting the left ventricle. The patient underwent cardiac surgery due to the lead perforation as also as aortic valve replacement due to concomitant severe aortic valve stenosis. Discussion: The presented case report is a rare case of lead perforation through the LV and illustrates that lead perforation can still occur even after placement of the RV lead in septal position and even through the thick ventricular wall.